Transforming Homoeopathic Education: The Impact of NCH Reforms (Homoeopathy for All, 2025)
In recent years, the field of  Homoeopathy in India has undergone  significant transformation, primarily  driven by the establishment of  the National Commission for  Homoeopathy (NCH) in 2020.  This regulatory body, created  under the National Commission  for Homoeopathy Act 2020, has  spearheaded a series of reforms  aimed at enhancing the quality and  integrity of Homoeopathy education  and practice. These changes  promise to elevate the standards  of Homoeopathy, ensuring its  practitioners are well-equipped  to meet contemporary healthcare  challenges. The NCH is founded with a  vision, that is, to promote high quality and ethical practices in  Homoeopathy and to ensure the  safety and well-being of patients.  By setting rigorous benchmarks  for homoeopathic education and  facilitating the development of  competent professionals, the NCH  envisaged effective contribution  of Homoeopathy into the national  healthcare system.
Keywords: New Education Policy; simulated environments; challenges; NTET Examination